NEWLY COMMISSIONED NAVAL OFFICER'S GUIDE / CDR SAMANTHA A. O'NEIL, USN - O'Neil, Samantha A. (Blue & gold professional library, 2025)
"Like the second edition, this edition focuses on basic leadership principles, etiquette, management, and practical advice for the new officer in a training pipeline or at the start of their first division officer tour"-- Provided by publisher